Shipping Emission Control Area Optimization Considering Carbon Emission Reduction - Zhuge, Dan; Wang, Shuaian; Zhen, Lu (Operations Research, 2024)
Managing Shipping Emission Control Areas The design of emission control areas (ECAs) is crucial for reducing global shipping emissions and protecting the environment. In “Shipping Emission Control Area Optimization Considering Carbon Emission Reduction,” Zhuge, Wang, and Zhen focus on the ECA optimization problem for sailing legs with ECAs. First, a case with a no-ECA policy and a case with the current ECA policy are discussed. Then, two new voyage-dependent ECA policies with sulfur limits, designated sailing paths, and speed limits are proposed, under which Stackelberg game models with the ECA regulator and a shipping company are developed. The authors extend the research problem from a sailing leg to a shipping network to improve the practicality of the findings. They also develop a dynamic programming-based algorithm to optimize the ECA policies for the shipping network from the perspective of the ECA regulator. The effectiveness of the proposed policies in reducing social costs is validated by numerical experiments.